The Influence of The Blended Learning Website Based on Creativity in Supporting Students Learning Basic Math - Hermanto, Hermanto; Fauzah, Ana (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This research aims to demonstrate the impact of implementing a Website-based Blended Learning method in enhancing student creativity to support basic mathematics learning. The method used in this study employs the ADDIE development model with 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The resulting learning product underwent validity testing by experts and practicality assessment by students. The products created through student creativity were evaluated using a Paired-sample T-Test to determine whether they were flexible, novel, and elaborative in relation to technological advancements. Research results calculated using SPSS 23 show that the product's practicality score is 0.989, meaning the product is deemed suitable with a "very good" category. The learning model, in the form of a website-based Blended Learning model, proved to be valid and practical when tested based on learning indicators (face-to-face and online), learning materials, and learning media. Consequently, this model is effective in influencing the development of student creativity in studying basic mathematics